Optimalisasi Pengumpanan Crusher dan Analisis Regresi Multivariat Terhadap Waktu Kerja Untuk Meminimalisir Losstime Agar Tercapai Target Produksi 300.000 Ton pada Penambangan Batu Granit Di PT. Trimegah Perkasa Utama - Ersila Maharani; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. PT. Trimegah Perkasa Utama is one private company engaged in the contracting of granite mining. In the mining process, PT. Trimegah Perkasa Utama aims to produce 300,000 tons in a month. However, based on actual production data in January - March 2019 the production target has not been achieved. Based on the results of field observations, it was found that one of the factors which cause the production target has not to be achieved is the number of obstacles that occur in loading hauling equipment and primary crusher units. Therefore, the Overall Equipment Effectiveness method is used to optimize the crusher feed and the Multivariate Analysis method to get the optimum time of loss time. Based on the research results obtained the equation model of time production loading hauling activities, Nordberg primary crusher, and Jaques primary crusher are Y = -326,865 + 34.28567 X1 + 564.6184 X2 + 748.8142 X3. The feed value production by optimization with the OEE method is 404,607,805 tons and the equation model of the idle time and delay time for the production of granite from each unit of the primary crusher is Y = 10115,19 - 259.22 X1 - 296,443 X2. In Jaques and Y units = 7873,46 - 60,069 X1 - 283,198 X2 in Nordberg unitsKeywords: Granit, Jaques Primary Crusher, Multivariate, Nordberg Primary Crusher, Optimalisasi Produksi